Intrinsic Phase Stability and Inherent Bandgap of Formamidinium Lead Triiodide Perovskite Single Crystals. (10th November 2022) - Chen, Liang; Yoo, Jin Wook; Hu, Manman; Lee, Seung‐Un; Seok, Sang Il
Abstract: Understanding the intrinsic phase stability and inherent band gap of formamidinium lead triiodide (FAPbI3 ) perovskites is crucial to further improve the performance of perovskite solar cells (PSCs). Herein, we explored the α‐ to δ‐phase transition and band gap of FAPbI3 single crystals grown by an inverse temperature solubility method. We found that the residual γ‐butyrolactone solvents in the inner empty space of the FAPbI3 single crystal accelerate the phase transition at kinetics. By adopting 2‐methoxyethanol as the solvent, over 2000 h of stable α‐FAPbI3 crystals could be acquired. This proves that although FAPbI3 is regarded as unstable at thermodynamics, it could own excellent kinetic stability without any doping or additives because of the slow solid to solid phase transition instead of the fast phase transition assisted by the solvents. Furthermore, we revealed that the bulk FAPbI3 single crystal with a size above 100 μm can have an inherent band gap of 1.41 eV. Thus, our work provides key scientific guidance for high‐performance FAPbI3 ‐based PSCs. Abstract : The residual γ‐butyrolactone (GBL) solvent molecules inside the void of α‐FAPbI3 single crystals promote the phase transition kinetics (2). By adopting the 2‐methoxyethanol (2‐ME) as solvent, highly stable α‐FAPbI3 crystals could be acquired due to slow solid to solid phase transition (1). α‐FAPbI3 with crystal size above 100 μm has an inherent 1.41 eV band gap.